Evaluation of Chilled Dog Semen Extended With Sperm Activator - Martínez-Barbitta, Marcelo; Rivera Salinas, Claudio (Frontiers in Veterinary Science, 2022)
Within modern biotechnology, different tools have been developed to maximize canine semen conservation protocol to optimizing reproductive results and making their handling more flexible. The survival of refrigerated semen has been prolonged from 2-3d with the first basic diluents, to 10-14d using the most modern extenders. However, their main limitation is that sperm quality decreases during cold storage. Semen activators (SA) have been produced to provide the molecules necessary to maximize the sperm survival and quality with the aim to enhance fertility and prolificacy. In this study, the effect of SA was recorded by daily evaluation of chilled semen 14d. Six adult healthy Neapolitan Mastiff dogs, were used as donors and the semen was manually collected. Spermatozoa-rich fractions of each suject was chilled using a new generation extender for long periods of time (d0) starting from the d1 to d14, different aliquot, were evaluated daily for motility vigor, morphology and membrane integrity. The initial sperm concentration of extended semen was 417.3±170.4x106/mL (mean±SEM), 85.89±4.76% MNS (morphologically normal sperm), 84.47±5.22 % vital sperm and pH 6.2±2.8. The initial vigor was 3.83±0.48, but after one min with SA, it rose to 4.45 ± 0.45 (P<0.001). The semen motility parameter increase significantly (P<0.05) in experimental trial, respect to control, starting to d2 at finish. The vigor analysis significantly increase in experimental trial (P<0.05) during the most day of the study. For evaluate the semen characteristics over time, the experiment was divided into T1 (d0-d5), T2 (d6-d10) and T3 (d11-d14) (P<0.001) in evaluation of morphology and membrane stability. The MNS reached 70% at d10 and finally 65% at d14, being considered normal and possibly fertile. With Host-s, 65% of MNS were also achieved at d14. The presence of glucose and fructose in the diluents used for refrigeration can exert very important effects given the fact that metabolic routes have been found in both sugars, providing both different and complementing effects. It can be concluded that the use of SA prior to artificial insemination improves the quality of chilled semen significantly, although it does not reverse the effects of deterioration due to cellular metabolism over time.